Mu opioid receptor mRNA overexpression predicts poor prognosis among 18 common solid cancers: A pan-cancer analysis - Sun, Wei; Zhuang, Shaohui; Cheng, Minghua; Qiu, Zeting (Frontiers in Oncology, 2023)
Background: Opioids are widely used for patients with solid tumors during surgery and for cancer pain relief. We conducted a pan-cancer genomic analysis to investigate the prognostic features of Mu opioid receptor (MOR) mRNA expression across 18 primary solid cancers. Methods: All the data of cancer with MOR mRNA were retrieved from cBioPortal for Cancer Genomics. Logistic regression was used to determine the associations between MOR mRNA expression and clinicopathological features. Log-rank test and Cox regression was used for survival analysis. Subgroup analysis and propensity score matching were also carried out. Results: 7,274 patients, including 1,112 patients with positive MOR mRNA expression, were included for data analyses. Positive MOR mRNA expression was associated with more advanced stage of T (adjusted Odds ratio [OR], 1.176; 95% confidence interval [CI], 1.022-1.354; P=0.024), M (adjusted OR, 1.548; 95% CI, 1.095-2.189; P=0.013) except N (adjusted OR, 1.145; 95% CI, 0.975-1.346; P=0.101), and worse prognosis for overall survival (Hazard ratio [HR] 1.347, 95% CI 1.200-1.512, P<0.001), progression-free survival (HR 1.359, 95% CI 1.220-1.513, P<0.001), disease-free survival (HR 1.269, 95% CI 1.016-1.585, P<0.001) and disease-specific survival (HR 1.474, 95% CI 1.284-1.693, P<0.001). Patients with positive MOR mRNA expression tended to be classified as tumor microenvironment immune types II, representing low PD-L1 and low CD8A expression. Conclusion: MOR mRNA overexpression is associated with poor prognosis and poor response to PD-L1 therapy.